Machaut - Reaney, Gilbert (London Oxford university press, 1971)
This short book concentrates on Machaut's music, rather than his life. Reaney looks at each of the genres that Machaut composed (Virelais, Motet, Ballade, etc.) as well as his Messe de Notre Dame and Hocketus, delving into the stylistic features of each and the techniques Machaut uses. Reaney also comments on how these pieces fit into both the established styles and the emerging Ars Nova. The discussions are fairly technical, with plenty of musical examples.